Urbanization: Planting Forests in Pots - SADRI HOSSEIN (Journal of Contemporary Urban Affairs, 2018)
Taking plants from their original habitat and keeping them in pots is an illustrative example of manmade, power-oriented and unnatural habitation. Naturally, a plant cannot survive in a segregated environment of a pot. For this reason, diverse supportive activities such as watering, feeding or protecting must be planned. These supplying infrastructures create a great power for the caretaker over the life of the potted plant. Using the example of potted plants, this article tries to shed light on the social and ecological problems of urbanization.